The Dredger's Daughter: Courtship and Marriage in the Baptist Community of Welland, Ontario, 1934-1944 - Gidney, Catherine (Labour / Le Travail, 2004)
In 1924 sixteen-year-old Kay Chetley along with her parents Jennie and Robert, and her sister Roberta, moved to the industrial city of Welland, Ontario. Kay was raised in east Saint John, New Brunswick where her father worked as a stationary engineer on dredging barges. Her mother, from a farming family in Petitcodiac, New Brunswick, had been a primary school teacher until her marriage. The family's economic status thus ranged between the artisan class and the emerging lower-middle class. To maintain that position, Kay's father moved the family to Ontario so that he could take up work in the construction of the new canal. Welland, however, soon became the setting for Kay's courtship, wedding, her first years as a married wom[a]n, and her subsequent years as a mother. This typical female life-cycle was played out not only within a tight-knit nuclear family, the dominant familial form in the early 20th century, but also within the community of First Baptist Church, Welland. Kay's life thus provides an illustration of the interconnectedness of religion, family, courtship, leisure, and work in one Ontario industrial community. The core of this study is constructed around a series of five-year diaries left by Kay Chetley. ...The diaries cover the bulk of the period from 1934 to 1944 and offer a few lines detailing Kay's activities each day. –Author's introduction